Extended metasurface spin functionalities from rotation of elements - Wei, Minggui (2023)
Metasurfaces are a class of planar optical components that are engineered to manipulate electromagnetic waves, including their spin states in terms of circular polarizations. For example, the Pancharatnam–Berry (PB) phase has been exploited in metasurfaces for various spin functionalities, but these spin functionalities, exhibit conjugate relations for spin states. Recent advances combining the PB phase and propagation phase have implemented completely independent spin functionalities for spin states. However, the spin functionalities are fixed once the metasurfaces are designed. Here, this work proposes and demonstrates that the spin functionalities designed from the PB phase and propagation phase can be further extended by simply rotating the elements in a metasurface. This extension is based on a relationship between phase profiles of spin states that are acquired before and after the rotation. Proof-of-concept demonstrations are performed for the extended spin functionalities, including the conversion from spin angular momentum to orbital angular momentum, and spin-dependent holograms. This extension may find use in relevant applications such as polarized display and dual-polarized holography.